Live-Cell Imaging of Physiologically Relevant Metal Ions Using Genetically Encoded FRET-Based Probes - Helmut Bischof; Sandra Burgstaller; Markus Waldeck-Weiermair; Thomas Rauter; Maximilian Schinagl; Jeta Ramadani-Muja; Wolfgang F. Graier; Roland Malli (Cells, 2019)
Essential biochemical reactions and processes within living organisms are coupled to subcellular fluctuations of metal ions. Disturbances in cellular metal ion homeostasis are frequently associated with pathological alterations, including neurotoxicity causing neurodegeneration, as well as metabolic disorders or cancer. Considering these important aspects of the cellular metal ion homeostasis in health and disease, measurements of subcellular ion signals are of broad scientific interest. The investigation of the cellular ion homeostasis using classical biochemical methods is quite difficult, often even not feasible or requires large cell numbers. Here, we report of genetically encoded fluorescent probes that enable the visualization of metal ion dynamics within individual living cells and their organelles with high temporal and spatial resolution. Generally, these probes consist of specific ion binding domains fused to fluorescent protein(s), altering their fluorescent properties upon ion binding. This review focuses on the functionality and potential of these genetically encoded fluorescent tools which enable monitoring (sub)cellular concentrations of alkali metals such as K+, alkaline earth metals including Mg2+ and Ca2+, and transition metals including Cu+/Cu2+ and Zn2+. Moreover, we discuss possible approaches for the development and application of novel metal ion biosensors for Fe2+/Fe3+, Mn2+ and Na+.